Simple UV Spectrophotometric Method for the Determination of Fluvastatin Sodium in Bulk and Pharmaceutical Formulations - J. Saminathan; A. S. Sankar; K. Anandakumar; T. Vetrichelvan (E-Journal of Chemistry)
A simple and cost effective spectrophotometric method is described for the determination of fluvastatin sodium in pure form and in pharmaceutical formulations. When the drug reacts with sodium hydroxide shows absorption maximum at 304 nm and obeys beer's law in the concentration range 5-25 µg mL-1. The absorbance was found to increase linearly with increasing concentration of FVS, which is corroborated by the calculated correlation coefficient value of 0.9999 (n=5). The apparent molar absorptivity and sandell sensitivity were 1.1905×104 and 0.0368844 µg cm-2 cm respectively. The slope and intercept of the equation of the regression line are 0.027112 and 0.003539 respectively. The limit of detection and limit of quantification was found to be 0.0811 µg mL-1 & 0.2460 µg mL-1. The validity of the described procedure was assessed. Statistical analysis of the result has been carried out revealing high accuracy and good precision. The proposed method was successfully applied to the determination of FVS in pharmaceutical formulations without any interference from common excipients. The relative standard deviations were ≤ 0.937%, with recoveries of 98.60% -101.70%.